5y(2y+5)-2y(8y-5)=-4y(2y-9)-(y-50)

Simple and best practice solution for 5y(2y+5)-2y(8y-5)=-4y(2y-9)-(y-50) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5y(2y+5)-2y(8y-5)=-4y(2y-9)-(y-50) equation:



5y(2y+5)-2y(8y-5)=-4y(2y-9)-(y-50)
We move all terms to the left:
5y(2y+5)-2y(8y-5)-(-4y(2y-9)-(y-50))=0
We multiply parentheses
10y^2-16y^2+25y+10y-(-4y(2y-9)-(y-50))=0
We calculate terms in parentheses: -(-4y(2y-9)-(y-50)), so:
-4y(2y-9)-(y-50)
We multiply parentheses
-8y^2+36y-(y-50)
We get rid of parentheses
-8y^2+36y-y+50
We add all the numbers together, and all the variables
-8y^2+35y+50
Back to the equation:
-(-8y^2+35y+50)
We add all the numbers together, and all the variables
-6y^2-(-8y^2+35y+50)+35y=0
We get rid of parentheses
-6y^2+8y^2-35y+35y-50=0
We add all the numbers together, and all the variables
2y^2-50=0
a = 2; b = 0; c = -50;
Δ = b2-4ac
Δ = 02-4·2·(-50)
Δ = 400
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$y_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$y_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{400}=20$
$y_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(0)-20}{2*2}=\frac{-20}{4} =-5 $
$y_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(0)+20}{2*2}=\frac{20}{4} =5 $

See similar equations:

| y+3*18-18=90 | | -5g+23=-188 | | 8x-14=-50 | | 14=v/2+11 | | x÷2=8÷x | | v/4-16=18 | | 3x+8=5x+24 | | -2+c=9 | | 8-k=-6 | | -6x+3-2x=-5+5+x | | -23=x-24 | | 2^2x=21 | | r-3=-5r+6r-3 | | 8n-6=-3n-6-5n | | 2u=14/3 | | 6-x=x-2-2x | | 9=3u+6 | | 3/2=15/x | | 2-2n+8=10-2n | | 2(3n-1)+3=-4+6n+5 | | 5+2n-4n=-13+4n | | 4x(x-7)+5x(2x+3)=13(x^2-x+2)-10 | | 17-20=(-3-5q)4 | | 6x-2=-11+1+6x+8 | | -5+12-7x=-3(5x+8) | | 1.25k=7.5 | | 12p-19p=14 | | 15•20=12y | | 3|4x+2|=6 | | (Y^3+1)-((y^2+1)+(3y-7))=0 | | 12.5=s+15.7 | | (4x-2)^2=36x^2 |

Equations solver categories